A two‐centre comparative evaluation of new automated assays for von Willebrand factor ristocetin cofactor activity and antigen. (12th September 2013) - Stufano, F.; Lawrie, A. S.; La Marca, S.; Berbenni, C.; Baronciani, L.; Peyvandi, F.
Summary von Willebrand disease (VWD) is caused by a quantitative and/or qualitative deficiency of the von Willebrand factor (VWF). The laboratory diagnosis of VWD is dependent on the measurement of VWF antigen (VWF:Ag) and ristocetin cofactor activity (VWF:RCo). The aim of this study was to undertake a two‐centre evaluation of two new automated VWF:Ag and VWF:RCo assays systems from Instrumentation Laboratory (Bedford, USA). Using the two new analytical systems that operated with different detection principles: immunoturbidimetric (TOP500 analyser) and chemiluminescent (AcuStar analyser), VWF:Ag and VWF:RCo levels were determined in samples from 171 healthy normal subjects, 80 VWD patients (16 type 1, 58 type 2 and 6 type 3) and 7 acquired von Willebrand syndrome patients. With commercial lyophilized normal and pathological plasmas VWF: Ag and VWF:RCo assays performed on both analysers exhibited low levels of inter‐assay imprecision (AcuStar: CV% range 3.3–6.9; TOP500: CV% range 2.6–6.3). Samples from normal healthy subjects (range: VWF:Ag 44.6–173.9 IU dL−1; VWF:RCo 43.1–191.5 IU dL−1) and patients (range: VWF:Ag <0.3–115.1 IU dL−1; VWF:RCo <0.5–57.2 IU dL−1) showed a good correlation between the two VWF:Ag and VWF:RCo methods (rs = 0.92 and 0.82 respectively), with only a few inconsistent cases among the patients' samples evaluated. The chemiluminescent assays had a lower limit of detection for both VWF:Ag and VWF:RCo compared to immunoturbidimetric tests (0.3 IU dL−1 vs. 2.2 IU dL−1 and 0.5 IU dL−1 vs. 4.4 IU dL−1 respectively). The TOP500 and AcuStar VWF:Ag and VWF:RCo assays were precise and compare well between centres, making these systems suitable for the diagnosis of VWD in non‐specialized and reference laboratories.